The Concrete Effective Width of a Composite I Girder with Numerous Contact Points as Shear Connectors - Alaa Hasan; Moaid Subh; George Wardeh (Applied Mechanics, 2024)
Due to the shear strain in the plane of the slab, the parts of the slab remote from the steel beam lag behind the part of the slab located in its proximity. This shear lag effect causes a non-uniform stress distribution across the width of the slab. As a result, several standards have introduced the concept of an effective flange width to simplify the analysis of stress distribution across the width of composite beams. Both the computed ultimate moment and serviceability limit states are directly impacted by the effective width. The effect of using a large number of contact points as shear connectors on the effective width of a steel beam flange has not been investigated. A three-dimensional finite element analysis is carried out in this paper. The ABAQUS software (version 6.14) is used for this purpose, where several variables are considered, including the surface area connecting the steel beam and concrete slab, the transverse space, and the number of shear connectors. It was discovered that the number of shear connectors on the steel beam flange has a major impact on the effective width. The many connectors work together to provide a shear surface that improves the effective width by lowering the value of the shear lag.